Egypt and Sudan Inception Workshop on the CGIAR F2R-CWANA Initiative - ICARDA, Communication Team (International Center for Agricultural Research in the Dry Areas, 2022)
Brochures for the events to celebrate the launch of the CGIAR Regional Integrated Initiative F2R-CWANA in the key countries of Morocco (17th May), Uzbekistan (17th June), Egypt and Sudan (29th June) and Lebanon and Syria (4th July) with keys NARES and other partners and stakeholders. This record is for the event that was held in Egypt and included a focus on Sudan.